Design and Development of RC Railed Robot for Coffee Nursery Logistics - Marivic Gatan Dizon; Carlo Tan Sevillano; Mark Anthony Timanel Cabaluna (National Research and Innovation Agency, 2014)
The Remote Controlled (RC) Railed Robot was designed and developed to transfer polybags from manual operation to an automated logistic system. Gizduino microcontroller was used to read and interpret commands sent and received by the transceivers to the robot and a remote to command instructions to the robot.The project was tested and evaluated at the Coffee Nursery of Cavite State University by determining the speed of the robot, the effectiveness of the remote control and the accuracy of the robot to lift a pallet and place it into an empty space.Results showed that the robot was able to receive and interpret commands provided by the remote control as well as perform the tasks successfully.The most significant recommendation was to use a counterweight at the rear side of the robot to avoid unnecessary derailments of the robot if lifting heavier or greater number of pallets is desired.